Chemical isotope labeling exposome (CIL-EXPOSOME) : one high-throughput platform for human urinary global exposome characterization - Jia, Shenglan (2019)
Human exposure to hundreds of chemicals, a primary component of the exposome, has been associated with many diseases. Urinary biomarkers of these chemicals are commonly monitored to quantify their exposure. However, because of low concentrations and the great variability in physicochemical properties of exposure biomarkers, exposome research has been limited by low-throughput and costly methods. Here, we developed a sensitive and high-throughput exposome analytical platform (CIL-EXPOSOME) by isotopically labeling urinary biomarkers with common functional groups (phenolic hydroxyl/carboxyl/primary amine). After a simple cleanup, we used mass spectrometry to perform a screening for both targeted and untargeted biomarkers, which was further processed by an automatic computational pipeline method for qualification and quantification. This platform has effectively introduced an isotope tag for the absolute quantification of biomarkers and has improved sensitivity of 2−1184 fold compared to existing methods. For putative identification, we built a database of 818 urinary biomarkers with MS/MS fragmentation information from either standards or in silico predictions. Using this platform, we have found 671 urinary exposure biomarker candidates from a 2 mL pooled urine sample. The exposome data acquisition and analysis time has also been greatly shortened. The results showed that CILEXPOSOME is a useful tool for global exposome analysis of complex samples.